Rapid Transcriptional Reprogramming Associated With Heat Stress-Induced Unfolded Protein Response in Developing Brassica napus Anthers - Lohani, Neeta; Singh, Mohan B.; Bhalla, Prem L. (Frontiers in Plant Science, 2022)
Climate change associated increases in the frequency and intensity of extreme temperature events negatively impact agricultural productivity and global food security. During the reproductive phase of a plant’s life cycle, such high temperatures hinder pollen development, preventing fertilization, and seed formation. At the molecular level, heat stress-induced accumulation of misfolded proteins activates a signaling pathway called unfolded protein response (UPR) in the endoplasmic reticulum (ER) and the cytoplasm to enhance the protein folding capacity of the cell. Here, we report transcriptional responses of Brassica napus anthers exposed to high temperature for 5, 15, and 30 min to decipher the rapid transcriptional reprogramming associated with the unfolded protein response. Functional classification of the upregulated transcripts highlighted rapid activation of the ER-UPR signaling pathway mediated by ER membrane-anchored transcription factor within 5 min of heat stress exposure. KEGG pathway enrichment analysis also identified “Protein processing in ER” as the most significantly enriched pathway, indicating that the unfolded protein response (UPR) is an immediate heat stress-responsive pathway during B. napus anther development. Five minutes of heat stress also led to robust induction of the cytosolic HSF-HSP heat response network. Our results present a perspective of the rapid and massive transcriptional reprogramming during heat stress in pollen development and highlight the need for investigating the nature and function of very early stress-responsive networks in plant cells. Research focusing on very early molecular responses of plant cells to external stresses has the potential to reveal new stress-responsive gene networks that can be explored further for developing climate change resilient crops.